(3)H-Noradrenaline-accumulating ability of cholinergic nerve terminals in cat sympathetic ganglia - Graham, J. D. P. (1971)
1. After incubation of pieces of cat posterior mesenteric ganglion in [(3)H]-noradrenaline solution, the localization of the isotope was assessed by electron-autoradiography. 2. Significantly higher concentrations of [(3)H]-noradrenaline were found over acetylcholinesterase-positive axons terminal on ganglion cells than in adjacent background areas. 3. [(3)H]-Noradrenaline was not accumulated by ganglion cells under these circumstances. 4. The significance of these findings in relation to previous physiological and pharmacological investigation is discussed.